Plan for a naval telegraph - Collis, F.
Plan of a naval telegraph to act both by day and night on board British ships.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Great Britain. -- Royal Navy; Military telegraph -- Great Britain